A leaf-molded transparent triboelectric nanogenerator for smart multifunctional applications. (February 2017) - Sun, Jian-Guo; Yang, Tse Ning; Kuo, I-Sung; Wu, Jyh-Ming; Wang, Chiu-Yen; Chen, Lih-Juann
Abstract: Transparent, flexible and highly efficient portable power sources are essential components of the next generation electronics and optoelectronic devices. However, complicated technology, expensive cost, environmental pollution and low-efficient output have limited its development. Herein, based on periodic contact/separation between human skin and the microstructured polydimethylsiloxane (PDMS) film, we demonstrate a transparent flexible triboelectric nanogenerator (TENG) through a relatively simple, low-cost, environmental-friendly and high-efficient method. For the first time, the natural leaves with rich surface textures were introduced to make microstructures on PDMS films as effective friction surface in the TENG. Furthermore, long silver nanowires (200 µm in length at least) through novel synthesis were assembled as high-performance electrode, resulting in the entirely flexible and transparent TENG. Owing to the unique design, the transparent flexible TENG was eventually obtained with an enhanced output (Voc=56 V; Isc=3.1 μA) and remarkable transparency (88%). Owing to compelling features of the TENG, a self-powered user-interactive wearable system was successfully established by integrating a flexible electrochromic device (ECD). The remarkable color-tunable ability via mechanical control of our system, highly inspired by chameleons, is potentially useful in military camouflage, monitoring human activity visually, as well as replacing performance of face change in Sichuan Opera. Therefore, this research is a substantial advancement toward the construction of transparent nanogenerator and its multifunctional applications in energy conversation, wearable electronics, healthcare, culture experience, and even environmental protection. Graphical abstract: A leaf-molded transparent triboelectric nanogenerator for smart multifunctional applications Highlights: Natural leaves were introduced as effectively novel mold to fabricate microstructured PDMS in TENG. Microstructured PDMS fabricated by leaf was proven to be a promising material for TNEG. A relatively fast, environmental friendly and facile galvanic displacement method was used to prepare Ag nanowires. Ultra-long silver nanowires were assembled as electrodes in TENG for achieving transparency and flexibility. The whole process of TENG fabrication is easy, cost-effective and environmental-friendly.